Brentuximab vedotin in patients aged 60 years or older with relapsed or refractory CD30-positive lymphomas: a retrospective evaluation of safety and efficacy. Issue 10 (October 2014) - Gopal, Ajay K.; Bartlett, Nancy L.; Forero-Torres, Andres; Younes, Anas; Chen, Robert; Friedberg, Jonathan W.; Matous, Jeffrey V.; Shustov, Andrei R.; Smith, Scott E.; Zain, Jasmine; O'Meara, Megan M.; Fanale, Michelle A.
Abstract Older adults constitute a significant proportion of the cancer population, but are underrepresented in clinical trials. We conducted a retrospective analysis of the safety and efficacy of brentuximab vedotin in adults ≥ 60 years with relapsed CD30-positive lymphomas. Baseline characteristics and safety data were compared for older (median age 66) and younger patients (< 60 years, median age 32). Exposure to brentuximab vedotin was comparable. Older patients had more preexisting conditions (median 11 vs. 6) and were receiving more concomitant medications (median 7.5 vs. 4). Higher rates of anemia (30% vs. 10%), peripheral sensory neuropathy (60% vs. 46%), fatigue (58% vs. 43%) and adverse events ≥ grade 3 (70% vs. 56%) occurred in older patients. Objective response rates were 56% and 100% in older patients with Hodgkin lymphoma and systemic anaplastic large cell lymphoma, respectively. With appropriate monitoring, brentuximab vedotin may represent a meaningful clinical option for older patients with relapsed CD30-positive lymphomas.